Transactions on Computational Collective Intelligence XII - Nguyen, Ngoc Thanh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
These transactions publish research in computer-based methods of computational collective intelligence (CCI) and their applications in a wide range of fields such as the semantic web, social networks, and multi-agent systems. TCCI strives to cover new methodological, theoretical and practical aspects of CCI understood as the form of intelligence that emerges from the collaboration and competition of many individuals (artificial and/or natural). The application of multiple computational intelligence technologies, such as fuzzy systems, evolutionary computation, neural systems, consensus theory, etc., aims to support human and other collective intelligence and to create new forms of CCI in natural and/or artificial systems. This twelfth issue contains 10 carefully selected and thoroughly revised contributions.
Formalisms and Tools for Knowledge Integration Using Relational Databases -- A Click stream Based Web Page Importance Metric for Customized Search Engines -- Opinion Analysis of Texts Extracted from the Social Web Contributions -- Time and Personality Based Behaviors under Cognitive Approach to Control the Negotiation Process with Incomplete Information -- Web Server Support for e-Customer Loyalty through QoS Differentiation -- Applying IPC-Based Clustering and Link Analysis to Patent Analysis on Thin-Film Solar Cell -- Multi-agent Virtual Machine Management Using the Lightweight Coordination Calculus -- Modelling Evacuation at Crisis Situations by Petri Net-Based Supervision -- Particle Swarm Optimization with Disagreements on Stagnation -- Evolutionary Algorithm with Geographic Heuristics for Urban Public Transportation.
Keywords: Computer science; Information systems; Artificial intelligence; Engineering; Computer Science; Artificial Intelligence (incl. Robotics).; Computational Intelligence; Information Systems and Communication Service